Initiated the GREAT GREAN WALL - an integrative Pan-African near-natural movement to overcome desertification, poverty & famine - Hars, Britta (2021)
Abstract: The Sahel zone is highly affected by climate change. Low rainfall and rising temperatures lead to drought and desertification of wide parts of the Sahel zone and subsequently to famine and poverty. To combat desertification and the concomitant loss of livability, the African Union initiated the Great Green Wall project - a program that enables local communities to sustainably improve livability, ensures food security and fuels economic growth. These massive efforts are made by conserving nature: sustainable land management is established, areas are reforested and diversity is significantly increased. The Poster illustrates, how community-lead, near-natural action can contribute to increase livability and economic growth by preserving ecosystems